1011 HETEROGENEOUS ARRHYTHMIC PHENOTYPE IN A CASE OF LEFT VENTRICULAR NON COMPACTION CARDIOMYOPATHY. (15th December 2022) - Ferrara, Nicola; Di Martino, Angelo; Bonanno, Salvatore; Crea, Pasquale; Carerj, Scipione; Luzza, Francesco; Dattilo, Giuseppe; Micari, Antonio; Di Bella, Gianluca
Abstract: A young 47 years old female patient was hospitalized in our department for recurrent traumatic syncopal episodes in order to undergo Head Up Tilt Test and Electrophysiology Study (EPS). Her ECG was normal and also transthoracic echocardiography didn't show pathological findings. 24 hour Holter ECG recording showed a short run of polymorphic ventricular tachycardia. Regarding familiar history her mother had died at a young age of sudden death. Head-up tilt test resulted negative for induced-syncope. During hospitalization the patient complained onset of malaise rapidly exiting in syncope: telemetry showed two pauses of 3.8 and 5.1 sec respectively, due to paroxysmal III degree atrio-ventricular block. The day after, the patient underwent electrophysiological study. During programmed ventricular stimulation from RV apex with train and V extrastimolous S1 300 S2 220 induction of syncopal ventricular fibrillation was observed, promptly treated with external DC shock. Cardiac MRI was performed showing diagnostic signs of Left Ventricular non-Compaction Cardiomyopathy. Considering the history of traumatic syncope the patient underwent dual chamber ICD implantation and was discharged. No clinical events in a 6 month follow-up. Genetical analysis was performed and we are waiting for the results. The term left ventricular non-compaction (LVNC) identifies a cardiomyopathy, characterized by intrauterine arrest of the compaction process of the ventricular myocardium during the end of the fourth week, thus leading to the development of prominent trabeculae of the left ventricle, deep intertrabecular recesses and a ventricular wall divider into two different layers of myocardium, the first compact, the other not. This nosological entity is difficult to classify (the European Society of Cardiology considers it as not classifiable among other cardiomyopathies, unlike the American Heart Association) mostly from the point of view of clinical implications, often unpredictable. In fact, we may have completely asymptomatic forms, which, according to some authors, should be considered as normal and completely benign variants, and various manifestations, in which the lack of compaction represents a morphological trait shared by phenotypically distinct forms of cardiomyopathy, such as hypertrophic, dilated and restrictive. LVNC carries an increased risk of ventricular dysfunction resulting in chronic heart failure, thromboembolic events and especially arrhythmic, often ventricular and life-threatening manifestations. A large spectrum of arrhythmias has been observed in patients with non-compact ventricles: in particular, supraventricular and ventricular tachycardias, Wolff-Parkinson-White (WPW) syndrome, but also bradyarrhythmias, which include sinus bradycardia, Sick Sinus Syndrome and various degrees of atrioventricular block, up to complete block. Ventricular tachycardias, including those that progress to ventricular fibrillation, occur in 38–47% of adult patients with LVNC, hence sudden death is often the cause of clinical presentation. Seen the features of the pathology, early diagnosis and family clinical evaluation are necessary aspects in patient management.